2016
DOI: 10.1371/journal.pmed.1002176
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Malaria Chemoprevention: An Evolving Research Paradigm

Abstract: Robert W. Snow discusses the importance of empirical evidence, such as that provided in the trial published this week by Milligan and colleagues, in guiding malaria control in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In this setting in rural Burkina Faso during the lean season, dietary diversity appeared to be a modifiable risk factor for stunting and chronic malnutrition, particularly among younger children. Interventions that address dietary diversity, such as unconditional cash transfers, community-based caregiver nutritional education 34 or promotion of improved infant and young child feeding practices, 35 should be considered in rural sub-Sahelian regions with seasonal malnutrition, as well as efforts to reduce the burden of infectious disease, such as seasonal malaria chemoprevention 36,37 or integrated community case management. 38 Improving dietary diversity will likely have greater effects on longer-term chronic malnutrition than acute malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting in rural Burkina Faso during the lean season, dietary diversity appeared to be a modifiable risk factor for stunting and chronic malnutrition, particularly among younger children. Interventions that address dietary diversity, such as unconditional cash transfers, community-based caregiver nutritional education 34 or promotion of improved infant and young child feeding practices, 35 should be considered in rural sub-Sahelian regions with seasonal malnutrition, as well as efforts to reduce the burden of infectious disease, such as seasonal malaria chemoprevention 36,37 or integrated community case management. 38 Improving dietary diversity will likely have greater effects on longer-term chronic malnutrition than acute malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review in 2011 identified 48 studies that evaluated the cost-effectiveness of malaria interventions [ 11 ], of which only two [ 10 , 12 ], were conducted among school-aged populations; as well as a cost analysis of a more recent school-based intervention in Kenya [ 13 ]. Better understanding the financial and economic costs of school-based interventions will help to inform ongoing questions of whether malaria control programmes can be channelled through schools, particularly in light of the availability of new preventive strategies such as seasonal malaria chemoprevention [ 14 , 15 ], and whether integrated programmes rather than single interventions should be implemented [ 10 , 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated in sub-Saharan Africa that seasonal malaria chemoprophylaxis (SMC) of children, the highest risk group for malaria in tropical Africa, can reduce malaria cases by 75%, is cost effective and safe and can be given by community health workers. 14 15 We propose to provide chemoprophylaxis to forest workers, the population group with the highest malaria risk in the GMS. In the proposed study, we compare chemoprophylaxis with an antimalarial drug, artemether-lumefantrine (AL) to a control agent, multivitamins.…”
Section: Introductionmentioning
confidence: 99%